Micro-/nanofibers prepared via co-assembly of paclitaxel and dextran. (10th February 2017) - Zhou, Tongtong; Zhu, Bangshang; Chen, Feng; Liu, Yongjia; Ren, Ning; Tang, Jing; Ma, Xiaoyu; Su, Yue; Zhu, Xinyuan
Highlights: Micro-/nanofibers prepared via co-assembly with paclitaxel and dextran. Paclitaxel was interacted with dextran through non-covalent interactions. The microfibers formed by twisted bundles of nanofibers. The paclitaxel/dextran fibers had good performance in drug delivery. Abstract: In this paper, we reported the preparation of micro-/nanofibers via co-assembly with paclitaxel (PTX) and dextran (DEX). The co-assembly fibers formed in PTX and DEX mixture solution via non-covalent interactions including hydrophilic/hydrophobic interactions and π-π stacking. The micro-/nanofibers could be obviously observed when the mixed solution became turbid and ivory-white in color. The properties of fibers were characterized by SEM, TEM, FTIR, DSC, XRD, in vitro release and MTT assay. The length of fibers could reach several centimeters. The diameter of microfibers and nanofibers was about 800 nm and 80 nm, respectively. In addition, the PTX loading efficiency was over 78% in co-assembly fibers and up to 84% when PTX and DEX (Mw: 40, 000) both were 2 mg/mL. The sustained drug release and low cytotoxicity in vitro of PTX/DEX fibers were also demonstrated. Therefore, we believe that PTX/DEX micro-/nanofibers would have great potential for drug delivery of PTX.